Assessment of Clinical Spectrum of Renal Diseases in children – A Descriptive Study at Benazir Bhutto Hospital, Rawalpindi - Mehvish Afridi, Sara Inayat, Zaib ., Saifullah Kakar, Anila Panezai, Sehrish Ghani (Journal of Rawalpindi Medical College, 2021)
Introduction: Childhood kidney diseases are a frequent presentation. Most of the affected pediatric populations are from under-developed and developing countries. Noting the epidemiology of childhood renal diseases is very important as it helps in health planning, allows for adequate resource allocation, and enables adequate renal services provision. This study aimed to determine the etiological spectrum of renal disease in pediatric patients. Material and Methods: A descriptive study was conducted in Benazir Bhutto Hospital, Rawalpindi over a period of 6 months. Ethical clearance was taken from the institutional review board and written informed consent was administered before enrollment of subject per study criteria. A total of 100 children of both genders, aged up to 12 years with the diagnosis of any renal disease condition were included in the study. Patients having other comorbidities like chronic liver disease and heart diseases were excluded. The study information as age, sex, detailed history, and physical examination, and details of laboratory investigations. Statistical analysis was conducted in SPSS version 20.0. Results: Mean age of patients was 2.1 years. Most patients had a fever, edema, burning micturition, and high blood pressure. In two-thirds of the children RFTs were deranged and 19.0% had positive urinary culture reports. The common kidney diseases were UTI (42.0%), nephrotic syndrome (29.0%), acute kidney injury/ disease (19.0%), and chronic kidney disease (6.0%). Conclusion: UTIs and nephrotic syndrome along with acute kidney injury were the main kidney conditions. Females were more likely to have UTIs whereas nephrotic syndrome was common in male children.